FEMALE BREADWINNING AND FAMILY RELATIONS AMONG MARKET WOMEN IN IBADAN, NIGERIA (2023)
Globally, Female Bread-winning (FBW), a phenomenon where the female contributes above fifty per cent of the household’s expenditures, is increasing. In Nigeria, this trend has occasioned a shift in traditional patriarchal norms. Previous studies on FBW largely focused on professional career women. However, there is paucity of evidence-based study on FBW among market women in Ibadan where there is a high incidence of FBW. This study was therefore designed to investigate the patterns and specific roles of female breadwinners,female breadwinners’ commitment to marital obligations, relationship with children and other kin; and coping strategies adopted among market women in Ibadan, Nigeria. Role Strain Theory guided the study, while the cross-sectional survey design was employed and mixed methods used. Stratified purposive sampling method was used to select three markets (Agbeni, Bodija and Gbagi) where there is a high concentration of female traders. On the second strata, three merchandise sections (fabrics, groceries and raw foodstuff) were selected. A sample of 903 respondents was drawn using Yamane’s (1967) formula, while the snowball technique was used for selecting interviewees and participants in FGD. Proportionate to size sampling method was used to administer a structured questionnaire to traders in Agbeni (289), Bodija (322) and Gbagi (292) markets. In-depth interviews were conducted with female breadwinners in each market and with selected spouses of female breadwinners. Six focus group discussions, two in each market, were held among female breadwinners. Quantitative data were analysed using descriptive statistics and Logistic regression at P≤0.05, while the qualitative data were content analysed. The majority (76.5%) of the respondents (aged 42.55±8.91 years) were married, and 49.1% had secondary education. FBW was high (52.0%). It was significantly associated with those with unemployed husbands (AOR=80.75) in general, and specifically with those who sold raw foodstuff: vegetables/pepper (OR =3.85), rice, beans and garri (OR=3.27). Female breadwinners played specific roles, particularly expenditures on transport fare (76.9%), children’s clothing (74.7%), feeding (56.4%), medical bills (46.5%) and children’s school fees (35.6%). Female breadwinners with unemployed husbands (OR=0.16) were less likely to be committed to marital obligations than those who lived apart from husbands (OR=0.26) and those with more than five children (OR=0.50). Cordial relationship with other kin is significantly associated with sellers in Agbeni market (OR=4.42), those who lived apart from husbands (OR=0.42) and those with unemployed husbands (OR=0.23). Thirty-seven percent had cordial relationship with other kin: and this had significant association with sellers in Agbeni market (OR=2.20), those who earned between N40001 and N60000 (OR=1.70) monthly and women living apart from husbands (OR=0.47). Indicated coping mechanisms include: trusting in God (79.7%), seeking counsel from relatives/friends (6.3%), keeping calm (5.0%) and using music therapy (2.9%). Husband’s infidelity, inability to provide for the family, gambling and drunkenness are some of the problems contributing to FBW. Socio-demographic variables, roles and commitments to marital obligations affected Female Breadwinning and family relations of market women in Ibadan. Social support mechanisms should be targeted at helping female breadwinners to minimise spousal conflicts arising from performingBreadwinning roles.